A programmed labour protocol for optimizing labour and delivery - Gupta, Kumud; Dubey, Smarika; Bhardwaj, Shital; Parmar, Meenal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objectives: 1) To evaluate the effect of programmed labor on duration of labor 2) To assess efficiency of analgesics in reducing severity of labor pains and 3) To find out any maternal and fetal/neonatal complications. Methods: 100 primigravida pregnant women meeting inclusion criteria admitted in labor room 50 were randomly enrolled in study group and 50 in control group. Results: Significant reduction in duration of active phase of labor and 43 (86%) cases had pain relief. Out of them 20 (40%) cases experienced excellent pain relief while in controls, only 22% had pain relief. Conclusions: Labour analgesia ensures pain relief, avoid maternal hyperventilation controls alteration of placental circulation thereby safe guarding the fetus against hypoxia. Thus programmed labor is easy, simple and effective method for painless delivery